A microanalytical investigation of feldspars in the Skaergaard intrusion, East Greenland : ternary feldspar compositional relations and lead isotopic geochemistry ... - Cho, June On Yee (University of British Columbia, 2019)
The Eocene Skaergaard intrusion, part of the East Greenland flood basalt province, is the type example of closed-system differentiation of basaltic magma. Studies of this remarkable layered intrusion have profoundly influenced our understanding of fundamental petrologic concepts. In this study, two complementary microanalytical applications of feldspar geochemistry are used to compare and evaluate (1) differentiation processes preserved in primocryst and interstitial feldspar, (2) the validity of the closed-system model for crystallization of the Skaergaard magma, and (3) the genetic link between the Skaergaard intrusion and the age-specific interval of the contemporaneous flood basalts. The spatially-controlled analyses include measurements of major and minor element oxide contents by electron microprobe and of lead (Pb) isotope ratios by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). The major element results (>2600 analyses) span nearly the entire range of permissible ternary ...